2012
DOI: 10.1039/c2cp23116f
|View full text |Cite
|
Sign up to set email alerts
|

Freezing water in no-man's land

Abstract: We report homogeneous ice nucleation rates between 202 K and 215 K, thereby reducing the measurement gap that previously existed between 203 K and 228 K. These temperatures are significantly below the homogenous freezing limit, T(H)≈ 235 K for bulk water, and well within no-man's land. The ice nucleation rates are determined by characterizing nanodroplets with radii between 3.2 and 5.8 nm produced in a supersonic nozzle using three techniques: (1) pressure trace measurements to determine the properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
265
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(291 citation statements)
references
References 68 publications
20
265
5
1
Order By: Relevance
“…At low temperature (T o210 K), the calculated ice nucleation rates differ only by one order of magnitude for different sizes, suggesting the suppression of the size dependence in ice nucleation rates in this regime. Such insensitivity to size is in quantitative agreement with recent experimental measurements of nucleation rates in water nanodroplets with radii between 3.2 and 5.8 nm, and between 202 and 215 K 8 . Figure 1 | Size dependence of ice nucleation rates in the mW water droplets at 230 K. The solid black squares denote the calculated ice nucleation rate within the mW droplets, the dash lines indicate the computed ice nucleation rate in the mW bulk water, the green circles denote the corrected ice nucleation rate by using the effective volume, and the purple diamonds represent the calculated nucleation rate in bulk liquid with the density matching that of the corresponding droplet.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…At low temperature (T o210 K), the calculated ice nucleation rates differ only by one order of magnitude for different sizes, suggesting the suppression of the size dependence in ice nucleation rates in this regime. Such insensitivity to size is in quantitative agreement with recent experimental measurements of nucleation rates in water nanodroplets with radii between 3.2 and 5.8 nm, and between 202 and 215 K 8 . Figure 1 | Size dependence of ice nucleation rates in the mW water droplets at 230 K. The solid black squares denote the calculated ice nucleation rate within the mW droplets, the dash lines indicate the computed ice nucleation rate in the mW bulk water, the green circles denote the corrected ice nucleation rate by using the effective volume, and the purple diamonds represent the calculated nucleation rate in bulk liquid with the density matching that of the corresponding droplet.…”
Section: Resultssupporting
confidence: 75%
“…Indeed, by suspending water clusters containing a few thousand molecules in a supersonic beam, liquid water was supercooled to a temperature as low as 200 K 7 . This technique also allowed experimentalists to extend the temperature range over which nucleation rates were measured 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present results of course do not exclude anomalous interfacial phenomena close to the homogeneous nucleation limit, or even at lower temperatures for microscopic droplets occurring in vapor-to-liquid nucleation studies. 4,38,39 The new data are intended to be used in an update 40 of the existing IAPWS standard for the surface tension of ordinary water. 27 In particular, the range of validity of correlation 2 will be extended to the metastable supercooled region, which is of high importance, e.g., in atmospheric modeling.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…2 It is known that water in clouds can persist in a supercooled liquid form at temperatures down to −38°C. 3 Manka et al 4 recently showed that liquid water nanodroplets rather than ice crystals form by homogeneous nucleation at temperatures down to −73°C. Reliable data for the surface tension of supercooled aqueous systems are also important in technical applications such as operation of wind turbines, 5 aircraft icing, 6 or design of secondary refrigeration systems operating with brine.…”
Section: ■ Introductionmentioning
confidence: 99%